2019
DOI: 10.1063/1.5085489
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic shock structures in magnetorotating relativistic plasmas with non-Maxwellian electrons

Abstract: Linear and nonlinear properties of electrostatic waves on the ion time scale in a collisional rotating magnetoplasma with warm relativistically streaming ions and non-Maxwellian electrons have been investigated here. In the weak nonlinearity limit, we have derived Zakharov-Kuznetsov-Burgers equation to study the shock wave propagation in dissipative magneto-rotating plasmas with non-Maxwellian electrons. It has been found that ion acoustic shock waves with kappa distributed electrons admit only compressive sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Significant modifications in the solitonic profiles were observed for the ion-acoustic waves due to additional positron component and reported the amplitude reduction of these waves for variation in positron concentration. Recently, numerous findings [14][15][16][17] have been identified to cover parametric and compositional analyses for ion-acoustic solitons in plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…Significant modifications in the solitonic profiles were observed for the ion-acoustic waves due to additional positron component and reported the amplitude reduction of these waves for variation in positron concentration. Recently, numerous findings [14][15][16][17] have been identified to cover parametric and compositional analyses for ion-acoustic solitons in plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Generally, DA and/or dust-ion-acoustic (DIA) solitary waves have been studied utilizing Maxwellian and non-Maxwellian distribution functions. [13][14][15][16][17][18][19] Indeed, it is by now shown that the presence of non-Maxwellian (nonthermal, suprathermal, trapped, nonextensive, etc.) particles modifies nonlinear solitary wave proprieties.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown by Henning et al [33] that the two electron population found in the Saturnian magnetosphere with superthermal features significantly modifies the propagation characteristics of electron Bernstein waves. Many researchers have employed kappa distributed charged species to investigate their effect on the propagation characteristics of nonlinear excitations in different types of plasma environments [34][35][36].…”
Section: Introductionmentioning
confidence: 99%